Evaluation of a Non‐destructive High‐voltage Technique for the Detection of Pinhole Leaks in Flexible and Semi‐rigid Packages for Foods. (29th August 2013) - Song, Yoon S.; Gera, Mohit; Jain, Bulbul; Koontz, John L.
<x xml:space="preserve">Abstract</x> This study evaluated the capabilities of a high‐voltage technique for the detection of pinhole leaks by using flexible pouches and semi‐rigid cups for foods. This evaluation was performed by measuring the discharge voltage when high voltages ranging from 0.25 to 10 kV were applied to sample packages. The results showed that package contact surface area, film thickness, food type and electrical conductivity are significant factors affecting the detection of pinhole leaks in flexible pouches by a high‐voltage leak detection (HVLD) system within the ranges tested (p < 0.05). For plastic cups with plastic‐laminated and foil‐laminated lids, the headspace inside a cup had the greatest effect followed by dielectric constant of lid films, electrical conductivity of foods and pinhole diameter (p < 0.01). In general, the HVLD system can detect pinholes as small as 10 µm in both plastic‐laminated and foil‐laminated pouches and lid cups, even at worst‐case scenario conditions, including liquid, semi‐solid and solid foods with 0.85 aw. Because of high voltages applied, however, delamination in foil‐laminated films occurred when an applied voltage was greater than 3.5 kV, which resulted in increased oxygen permeability. Statistical z‐test analysis of results from blind studies showed that the HVLD technique is significantly effective in determining defective pouches and cups with pinhole leaks as small as 10 µm (p < 0.05). Therefore, it can be concluded that the HVLD technique is a promising non‐destructive and on‐line method to detect pinhole defects, which may be applicable to a wide range of hermetically sealed packages. Copyright © 2013 John Wiley & Sons, Ltd.